Chikungunya Virus Infections Among Travelers–United States, 2010–2013 - Lindsey, Nicole P. (Am J Trop Med Hyg, 2015)
Chikungunya virus is an emerging threat to the United States because humans are amplifying hosts and competent mosquito vectors are present in many regions of the country. We identified laboratory-confirmed chikungunya virus infections with diagnostic testing performed in the United States from 2010 through 2013. We described the epidemiology of these cases and determined which were reported to ArboNET. From 2010 through 2013, 115 laboratory-confirmed chikungunya virus infections were identified. Among 55 cases with known travel history, 53 (96%) reported travel to Asia and 2 (4%) to Africa. No locally-acquired infections were identified. Six patients had detectable viremia after returning to the United States. Only 21% of identified cases were reported to ArboNET, with a median of 72 days between illness onset and reporting. Given the risk of introduction into the United States, healthcare providers and public health officials should be educated about the recognition, diagnosis, and timely reporting of chikungunya virus disease cases.